PENGARUH KEJELASAN SASARAN ANGGARAN DAN PENEKANAN ANGGARAN TERHADAP SENJANGAN ANGGARAN DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERASI (Studi Empiris pada SKPD Kabupaten Indragiri Hulu) - Wulandari, Widiya Restu; Surya, Raja Adri Satriawan; Paulus, Sem (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine and analyze the effect of goal clarity budget and emphasis budgets on budgetary slack with the organizational commitment as a moderating variable. This research data was obtained from the questionnaires which was distributed to all SKPD Indragiri Hulu with purposive sampling method.This study population was departments, agencies, and local government offices in district the indragiri hulu. The sample used in this study were 92 respondents. The method of analysis used for testing the hypothesis is simple linear regression analysis with the help of SPSS software version 20.0. Based on the results of hypothesis testing found that budget goal clarity significant effect on budgetary slack. Emphasis budget significant effect on budgetary slack. While the organizational commitment can moderate the effect of budget goal clarity on budgetary slack. Organizational commitment can also moderate the effect of emphasis budget on budgetary slack. Where the effect of budget goal clarity against budgetary slack shows coefficients ß1 negative for 0,774 with a significance of 0,000 < 0,05. The influence of the budget emphasis on budgetary slack shows coefficients ß2 negative for 0,627 with a significance of 0,000 < 0,05. While it, organizational commitment can moderate the effect of budget goal clarity on budgetary slack shows coefficients ß3 positive for 0.059 with a significance of 0,004 < 0,05. And organizational commitment can moderate the effect of the budget emphasis on budgetary slack shows coefficients ß4 positive for 0.039 with a significance of 0,001 < 0,05.Keywords : Budget goal clarity, budgetary emphasis, organizational commitment and budgetary slack